Anaesthetic Challenges in Pulmonary Alveolar Proteinosis: A Rare Case Report - Dasara Nongbet; Priyanka Dev; Vijay Noel Nongpiur; John Muchahary; Pranjal Kalita (Journal of Clinical and Diagnostic Research)
Pulmonary Alveolar Proteinosis (PAP) is a rare pulmonary disease characterised by the accumulation of surfactant within the alveoli, leading to impaired gas exchange. This case involves a 31-year-old male presenting with shortness of breath. Fine crackles were heard on auscultation, raising the suspicion of alveolar involvement. High-Resolution Computed Tomography (HRCT) of the chest revealed a “crazy paving” pattern in the bilateral lung parenchyma, a hallmark imaging finding in PAP. Histopathological analysis confirmed the diagnosis, showing alveoli filled with granular, eosinophilic, Periodic Acid Schiff (PAS)-positive material, indicative of surfactant accumulation. The patient was scheduled for Whole Lung Lavage (WLL), the standard therapeutic procedure for PAP, under General Anaesthesia (GA). A Double-lumen Endotracheal Tube (DLT) was employed to facilitate isolation of each lung, ensuring effective lavage of the affected lung while maintaining ventilation in the other. This case highlights the importance of a multidisciplinary approach, integrating clinical evaluation, advanced imaging, histopathology and specialised anaesthetic techniques in managing rare conditions like PAP. This comprehensive strategy aims to restore alveolar function and improve the patient’s respiratory status, underscoring the critical role of timely diagnosis and intervention in rare pulmonary disorders.